Pengaruh Kinerja Keuangan Terhadap Pertumbuhan Laba Perusahaan Sub-Sektor Otomotif Dan Komponen Di Bursa Efek Indonesia - Christina Simanjuntak; Rosalina Marpaung; Qoffariani Nur Fadila; Puput Almiah Br. Sinulangga; D Sakuntala (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2020)
This study aims to analyze the effect of current ratio, total asset turnover, dan debt to equity ratio to the profit growth at the companies automotive was listed on the Indonesia Stock Exchange. The samples used in this study were 5 automotive companies listed on the Indonesia Stock Exchange in the period 2006-2018. A method of data analysis in this study using multiple linear regression. empirical results show current ratio and debt to equity ratio variables have a positive and significant effect on profit growth, while total asset turnover not affect profit growth.